Mecanismos envolvidos na citotoxicidade de uma ditiolpirrolona obtida de Streptomyces sp. isolado da Ascídia Eudistoma vannamei - Abreu, Paula Araújo de (2013)
Ascidians and marine microorganisms are prolific producers of cytotoxic and antitumor compounds. As part of a study to examine Brazilian species, we examined microbiota associated with ascidian, Eudistoma vannamei as potential sources for active natural product leads Earlier revisions with this specie showed a potent anticanceractivity of its extract; and two unpublished staurosporines were isolated. Curiously, these classes of compounds are generally produced by bacteria. So, in order to evaluate the biomedical potential of these compounds the microbiota associated to the ascidian Eudistoma vannamei was investigated. From this effort we isolated a number of bacterial strains and after screening for cytotoxicity using a panel of tumor cell lines, we identified a Streptomyces sp.,that presented significant bioactivity. Using bioactivity fractionation, we identified the active compound as, dithiolopyrrolone N-(4,5-dihydro-5-oxo-1,2- dithiolo[4,3-b]pyrrol-6-yl)-N-methyl-formamide also know as VD846. The compound presented IC50 values ranging from 1.1 to 6.4 μM across a panel of cell lines. Further biological studies, indicated that this compound induced cell cycle arrest during mitosis, an observation that was confirmed by evaluating the effects on a series of cell lines using mitotic index analyses, flow cytometry, and confocal microscope. Western blot analyses indicated that cells treated with VD846 resulted in reduced expression of Plk1 and RhoA, proteins that are necessary for cleavage furrow assembly and exit from cytokinesis.